As(III, V) Uptake from Nanostructured Iron Oxides and Oxyhydroxides: The Complex Interplay between Sorbent Surface Chemistry and Arsenic Equilibria - Sanna Angotzi, Marco; Mameli, Valentina; Fantasia, Alessandra; Cara, Claudio; Secci, Fausto; Enzo, Stefano; Gerina, Marianna; Cannas, Carla (Nanomaterials (Basel, Switzerland), 2022)
Iron oxides/oxyhydroxides, namely maghemite, iron oxide-silica composite, akaganeite, and ferrihydrite, are studied for AsV and AsIII removal from water in the pH range 2-8. All sorbents were characterized for their structural, morphological, textural, and surface charge properties. The same experimental conditions for the batch tests permitted a direct comparison among the sorbents, particularly between the oxyhydroxides, known to be among the most promising As-removers but hardly compared in the literature. The tests revealed akaganeite to perform better in the whole pH range for AsV (max 89 mg g-1 at pH0 3) but to be also efficient toward AsIII (max 91 mg g-1 at pH0 3-8), for which the best sorbent was ferrihydrite (max 144 mg g-1 at pH0 8). Moreover, the study of the sorbents' surface chemistry under contact with arsenic and arsenic-free solutions allowed the understanding of its role in the arsenic uptake through electrophoretic light scattering and pH measurements. Indeed, the sorbent's ability to modify the starting pH was a crucial step in determining the removal of performances. The AsV initial concentration, contact time, ionic strength, and presence of competitors were also studied for akaganeite, the most promising remover, at pH0 3 and 8 to deepen the uptake mechanism.
Keywords: β-FeOOH; ferrihydrite; water remediation; arsenic; akaganeite; maghemite